Comparative study showing relevance of prosthesis diameter and hearing outcome in stapes surgery - Thangavel, Udayanila; Katakdhond, Harish Narasing; Dalmia, Deepak; Davange, Narsinha; Patni, Parth; Goyal, Rizul (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Otosclerosis presents as conductive hearing loss, stapedotomy is the treatment for otosclerosis, and different sizes of piston diameter are available for the procedure. Aims and objectives were to study and compare hearing improvement between the 0.4 and 0.6 mm sizes of teflon piston in stapedotomy. Methods: It was a prospective randomized controlled trial. Patients fulfilling inclusion criteria were subjected for small fenestra stapedotomy. Patients were divided into two groups after randomization into group A (with 0.4 mm piston diameter) and group B (with 0.6 mm piston diameter). The hearing outcome with standard audiological assessment was performed at one month and six months postoperatively. Results: Comparison of 1 month AB gap among the patients with 0.4 mm piston and 0.6 mm piston showed that there was no statistically significant difference among both the groups of patients (independent t test p value=0.699). Comparison of 6 month AB gap among the patients with 0.4 mm piston and 0.6 mm piston showed that there was no statistically significant difference among both the groups of patients (independent t test p value=0.54). Conclusions: There was no significant difference in hearing improvement among the individual methods (piston size 0.4 and 0.6) with each other both in 1 month post-operative and 6 month post-operative follow up. Hence, we conclude that there is no relevance of different diameter of teflon piston prosthesis (0.4 mm versus 0.6 mm) as far as hearing outcome is concerned.